Management of Fatigue in Persons with Multiple Sclerosis - Khan, Fary; Amatya, Bhasker; Galea, Mary (Frontiers in Neurology, 2014)
Fatigue is one of the most common symptoms of multiple sclerosis. Despite advances in pharmacological and non-pharmacological treatment, fatigue continues to be the disabling symptom in persons with MS, affecting almost eighty percent of persons with MS. In current practice, both pharmacological and non-pharmacological interventions are used in combination, encompassing a multidisciplinary approach. The body of research investigating the effect of these interventions is growing. This review systematically evaluated the existing evidence on the effectiveness and safety of different interventions currently applied for the management of fatigue in person with MS in improving patient outcomes, to guide treating clinicians